STRATEGIC MEASURES TOWARDS PROTECTING ENVIRONMENTAL HEALTH - Olanipekun, J. A. (European Scientific Journal, ESJ, 2013)
The paper posited from observations and media reports that Nigerian’s measures towards environmental health protection is poor. The paper reviewed the environmental health principles, practice, discussed the concerns of unhealthy environment and its threats to human existence, implications for emerging health policy and other challenges. It was therefore recommended that constant evaluation of the criteria for and implementation of health care delivery system should be focused. Health policies and interventions must be related to the assessment of the health risks and health outcomes. Collaborative partnerships focused on communities, local agencies and Non-Governmental Organization’s (NGO’s) services as relevant to environmental health protection should be highly concerned.